Serum magnesium level at 24 to less than 37 weeks: a prospective COHORT study predicting spontaneous preterm delivery - Astha,; Divya, (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
Background: Preterm labour is a leading cause of perinatal morbidity and mortality. Out of various causes, many macronutrients and micronutrients are said to have a role in pathogenesis of preterm labour, one of them is magnesium. Magnesium inhibits myometrial contractions by antagonizing calcium mediated uterine contractions. With advancement of pregnancy serum magnesium levels falls causing hyper excitability of neuromuscular junction bringing in uterine hyperactivity. The study was aimed to measure and compare the level of serum magnesium in preterm labour and normal pregnancy and to find the association of serum magnesium level with preterm labour. Methods: This cohort observational study was done in Department of Obstetrics and Gynaecology, King George's Medical University, Lucknow and eligible participants i.e., pregnant women with singleton gestation between 24 and <37 weeks of gestation were enrolled.112 women with preterm labour and 120 with no preterm labour were taken as study and control group respectively, serum magnesium level measured and followed till delivery. Results: The study showed mean serum magnesium level was 1.79±0.22 mg/dl in study group as compare to 1.98±0.25 mg/dl in control group and the difference was statistically significant (p<0.001). The value of Serum Magnesium below 1.885 mg/dl had a sensitivity of 64.8% and specificity of 66.1%. Conclusions: We can conclude that low serum magnesium is associated with preterm labour and serum magnesium estimation in pregnancy may be a valuable marker of predicting preterm labour.